Kontribusi Social Value, Atmosphere dan Food Quality dalam meningkatkan Revisit Intention Pelanggan - Frandita Ahmad Zulfadhli; Yadi Ernawadi (Journal of Management and Bussines (JOMB), 2024)
The aim of this research is to examine the influence of social values, atmosphere and food quality on the intention to return to visit through customer satisfaction at Eighteen Coffee. A total of 100 visitors who experienced visiting the Eighteen coffee shop participated in this research as respondents. The cross-sectional method was used to obtain data. The research instrument passed the validity and reliability tests. The data analysis technique used is Structural Equation Modeling (SEM) using the SmartPLS version 3.0 tool. Of the ten research hypotheses proposed, seven of them are supported by empirical data. Social values, food quality, and discovery have a positive effect on customer satisfaction. Furthermore, the atmosphere has a positive effect on intention to visit again. Then, customer satisfaction has a positive effect on intention to visit again. While mediating customer satisfaction, the influence of social value, atmosphere and food quality on intention to revisit. The results of this research provide benefits for further research and the management of the Eighteen coffee shop in designing marketing strategies that are relevant to the concept being measured. Keywords: Social Value, Atmosphere, Food Quality, Customer Satisfaction, Revisit Intention